A Personalized Muscle–Tendon Assessment and Exercise Prescription Concept Reduces Muscle–Tendon Imbalances in Female Adolescent Athletes - Theresa Domroes; Kolja Weidlich; Sebastian Bohm; Falk Mersmann; Adamantios Arampatzis (Sports Medicine - Open)
Abstract Background Imbalances between muscle strength and tendon stiffness influence the mechanical demand on the tendon (i.e., tendon strain) and may increase tendon injury risk. The purpose of this study was to identify muscle–tendon imbalances and to promote a more balanced musculotendinous adaptation through a personalized assessment and exercise prescription concept in female adolescent handball athletes (13–16 years). Methods At four measurement time points during a competitive season, we used dynamometry and ultrasonography to assess knee extensor muscle strength, patellar tendon stiffness and strain. Tendon micromorphology was assessed with a peak spatial frequency (PSF) analysis of proximal tendon ultrasound images. Muscle–tendon imbalances were identified based on tendon strain during maximum voluntary contractions. A control group (n = 15) followed their usual training. In the intervention group, athletes with a deficit in tendon stiffness (strain ≥ 9%; n = 6) or no muscle–tendon imbalances (strain between 4.5% and 9%; n = 15) performed exercises (3x/week for 32 weeks) with a personalized load to reach ~ 6.2% tendon strain to predominantly promote tendon or both muscle and tendon adaptation. Individuals with a muscle strength deficit (strain ≤ 4.5%; n = 1) trained with submaximal loads to failure to promote muscle strength. Results In the intervention group we found lower fluctuations of maximum tendon strain (p = 0.005) and a decrease in tendon strain over time (p = 0.010), which was more pronounced in individuals with initially high tendon strain. While there were no systematic changes in muscle strength or tendon stiffness at the group level (p > 0.05), the marked decrease in tendon strain in individuals with a deficit in tendon stiffness was caused by a predominant increase in tendon stiffness. Overall, the prevalence of muscle–tendon imbalances was reduced in the intervention group, while it temporarily increased in the control group. PSF did not differ between groups at baseline but decreased significantly in the intervention group (p = 0.013). Conclusions The findings suggest that the personalized concept is suitable to promote a more uniform adaptation of knee extensor muscle strength and patellar tendon stiffness and to reduce the prevalence of musculotendinous imbalances in female adolescent athletes, which may have important implications for tendon injury prevention. Trial Registration DRKS, DRKS00035110. Registered 20 September 2024–retrospectively registered, https://drks.de/search/de/trial/DRKS00035110 .